Before birth and beyond: Advance care planning in perinatal and neonatal palliative care – A scoping review - Maria Beatriz Mariano-Menezes; Paulo Reis-Pina (Palliative Medicine, 2026)
Background: Advance care planning is a core component of Palliative Care, yet how it is organized and used in practice remains variably described. Aim: To map how advance care planning is put into practice within Perinatal/Neonatal Palliative Care and identify contextual enablers and barriers across settings and stakeholder groups. Design: Scoping review registered on the Open Science Framework ( https://osf.io/c3mkx/overview ; May 2, 2025). Data sources: MEDLINE, Web of Science, and Scopus (2014–2024). Participants included parents/legal guardians, healthcare professionals, and infant/dyad record-based data eligible for Perinatal/Neonatal Palliative Care; Concept covered delivery, content, timing, documentation, and barriers/enablers; Context was perinatal/neonatal settings in any country. PRISMA-Scoping Review guidelines were followed; Joanna Briggs Institute critical appraisal tools were used. Data were synthesized narratively. Results: Ten studies were included, mostly from Europe. Advance care planning was consistently associated—descriptively—with clearer communication and more structured end-of-life decision-making, with sustained emphasis on infant comfort/symptom management. Where birth/comfort plans were standardized and accessible, documentation/implementation improved; a before–after analysis also reported gains in multidisciplinary communication, documentation of parents’ views, clarity of end-of-life status, and use of comfort-oriented regimens. Parents/families highlighted validation, preparedness, agency, and memory-making. Professional/service-level factors underscored training, templates, early referral, and parallel planning. Concordance and validated parent-reported measures were rarely quantified. Conclusions: Within Perinatal/Neonatal Palliative Care, advance care planning organizes communication/decisions while supporting infant comfort with standardized, shared plans. Practice should prioritize structured conversations, embedded documentation, early referral, and training; research should prospectively evaluate standardized pathways, measure parent-centered outcomes and concordance, and strengthen neonatal pharmacology.